An Explorative Study On Factors Associated With Neutropenia Onset And Severity Among Cancer Patients - Hassan, Bassam Abdul Rasool (2009)
the main objective of this study is to identify the main risk factors associated with the onset and severity of neutropenia and to determine the most common treatment used for neutropenia. An observational retrospective study using convenient sampling was carried out on solid tumor patients admitted to Penang Hospital between 2003 and 2006.